The Effect of Financial Literacy on Financial Behavior Moderated by Information Access - Zuraidah, Zuraidah; Nasution, Emmi Suryani (Universitas Serambi Mekkah, 2021)
The purpose of this study was to obtain empirical evidence of the effect of financial literacy on financial behavior moderated by the variable of access to information, in economics faculty students. The phenomenon of this research wanted to detect empirical evidence that students who were wellliterate with the support of access to sufficient information will have good financial behavior. The questionnaire distribution obtained a sample of 42 students of economics. This research used the regression analysis method with moderation. The results of the study indicated that financial literacy had an influence on students' financial behavior which was moderated by information access. Keywords: financial literacy, financial behavior, information access.